La ciencia española en la Segunda República y la historiografía - Ribagorda, Álvaro (REVISTA DE HISTORIOGRAFÍA (RevHisto), 2018)
Historiography has yet to pay enough attention to specificity of science during the Spanish Second Republic. The period has been diluted within general visions of the early twentieth-century Spanish History of Science. Here we review the literature and highlight the importance of developing a specific historiographical perspective on the topic.
Keywords: Science; JAE; University; scientists; Spanish Second Republic